PUBLICATIONS IN PERIODICALS OF UKRAINIAN TO PIDCARPATTYA POETRY OF THE ZORESLAV (STEPAN SABOL) - Rebryk, N. Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Literary reserve of the Zoreslav (Stepan Sabol) intersoldiery years is analyzed, that represented to the reader powerful perceptible and aesthetically beautiful animation in an organic value of the religious-christian spirit